Delving deep : techniques we wished we had known as emerging scholars - O'Kane, Paula; Busenbark, John R.; McKenny, Aaron F.; Paroutis, Sotirios (Research methodology in strategy and management, 2024)
Research Methodology in Strategy and Management advances understanding of the methods used to study organizations - including managers, strategies, and how firms succeed. Well-worn methods such as ordinary least squares regression are featured prominently in doctoral methods seminars around the world. On the other hand, newer and less familiar methodological considerations often receive uneven coverage. As a result, many scholars find themselves wishing they were familiar with techniques that were missed in their formal training. This volume explores such methods in depth, and the chapter authors answer questions such as what do researchers want to know more about? What is innovative and emerging that will change research in the future? What techniques are often overlooked that could open the door to new research questions or provide a more robust test of familiar questions? Delving Deep is a necessity for both experienced and new academics and researchers interested in the progression and cutting-edge studies of management, strategy, international business, entrepreneurship, and organization theory.